Yield and fruit quality of 'Gala' and 'Fuji' apple trees protected by white anti-hail net - Do Amarante C.V.T.* (2011)
Covering apple orchards with nets protects them from hailstorms but this changes the amount and quality of the light supplied to the trees. This study was carried out to assess the effects of shade provided by white protection net on yield and fruit quality of apple orchards in Southern Brazil, along three growing seasons (2002/2003, 2003/2004, and 2004/2005). 'Gala' and 'Fuji' apple trees (on MM111 rootstock, raised as slender spindles, with a spacing of 5.5. m × 3. m) were left uncovered (control trees) or covered with white net. The white net reduced the photosynthetically active radiation (λ= 400-700. nm) accumulated over the trees' canopy along a day by 18.4%, leading to a higher leaf chlorophyll content in both cultivars, and a higher specific leaf area in 'Gala'. The shade provided by the net did not affect yield and increased fruit average weight in both cultivars. At harvest, the number of seeds per fruit and severity of russet were not affected by netting in both cultivars, as well as the incidence of watercore in 'Fuji'. The main beneficial effects of the white net were the reduced incidence of sunburn on 'Gala', reduced incidence of bitter pit during cold storage in both cultivars, and reduced incidence of apple scab at harvest and of decay after cold storage in 'Fuji'. Fruit fly damage in 'Gala' (assessed in one season) was reduced by netting. However, netting affected negatively some fruit quality attributes. 'Gala' and 'Fuji' apples from trees protected by the net had a poor skin color (pale blush and a more intense green background color) at harvest. The net reduced flesh firmness and SSC, and increased the starch index of 'Gala' apples at harvest, and reduced flesh firmness and SSC, assessed after cold storage and shelf life, in fruits of both cultivars. © 2011 Elsevier B.V.